Novel Compound Missense and Intronic Splicing Mutation in ALDH18A1 Causes Autosomal Recessive Spastic Paraplegia - Chen, Yi-Jun; Zhang, Zai-Qiang; Wang, Meng-Wen; Qiu, Yu-Sen; Yuan, Ru-Ying; Dong, En-Lin; Zhao, Zhe; Zhou, Hai-Tao; Wang, Ning; Chen, Wan-Jin; Lin, Xiang (Frontiers in Neurology, 2021)
Background: Hereditary spastic paraplegia (HSP) caused by mutations in ALDH18A1 have been reported as spastic paraplegia 9 (SPG9), with autosomal dominant and autosomal recessive transmission (SPG9A and SPG9B). SPG9 is rare and has shown phenotypic and genotypic heterogeneity in previous reports. Methods: This study screened ALDH18A1 mutations in autosomal recessive HSP patients using combined whole exome sequencing and RNA splicing analysis. We conducted in silico investigations, co-segregation analysis, and ELISA-based analysis of P5CS (Δ1-pyrroline-5-carboxylate synthetase; encoded by ALDH18A1) concentration to validate the pathogenicity of the detected ALDH18A1 variants. All previously reported bi-allelic ALDH18A1 mutations and cases were reviewed to summarize the genetic and clinical features of ALDH18A1-related HSP. Results: A novel missense mutation c.880T>C, p.S294P and an intronic splicing mutation c.-28-13A>G were both detected in ALDH18A1 in an autosomal recessive family presenting with a complicated form HSP. ELISA assays revealed significantly decreased P5CS concentration in the proband’s plasma compared with that in the healthy controls. Moreover, review of previously reported recessive cases showed that SPG9B patients in our cohort presented with milder symptoms, i.e., later age at onset and without cognitive impairment. Conclusion: The present study expands the genetic and clinical spectrum of SPG9B caused by ALDH18A1 mutation. Our work defines new genetic variants to facilitate future diagnoses, in addition to demonstrating the highly informative value of splicing mutation prediction in the characterization of disease-related intronic variants.